Effect of Indian women’s exposure to warning messages on intention to quit smokeless tobacco - Begum, Shahina; Schensul, Jean J.; Nair, Saritha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Media campaigns have been shown to affect intention to quit the use of smoked tobacco and quit behaviour among men. However, despite warning messages on tobacco packages and delivered via mass media, such campaigns have had limited reach and effect on women’s use of smokeless tobacco (SLT) and SLT use among Indian women is increasing. This paper explores the association between selected warning messages conveyed through different media mechanisms and intention to quit smokeless tobacco among women of reproductive age in Mumbai. Methods: A cross-sectional community survey was conducted in a representative sample of 409 daily smokeless tobacco (SLT) women users aged 18- 40 years in a low-income community in Mumbai during 2011-2012. The paper utilizes information on socio-demographic characteristics, types of tobacco use, exposure to different types of warning messages and intention to quit collected through a researcher-administered structured questionnaire. Univariate and bivariate analysis were carried out to examine the influence of warning messages on intention to quit SLT use. Results: Half of the women correctly interpreted the image of scorpion on the SLT product as ‘causing cancer’. About 36% women were exposed to warning messages on television and 67% of women intended to quit SLT. Correct interpretation of the significance of the scorpion sign on SLT packets was not significantly associated with intention to quit SLT use. However, the likelihood of intention to quit was significantly higher among those who were exposed to warning messages on television than their counterparts. Conclusions: Since anti-tobacco campaigns on television were significantly associated with the intention to quit but warnings on package tobacco were not, expansion of anti-tobacco messaging on television targeted and tailored to women should further increase quit intentions and over time, with effective cessation programs in place, have an impact on quit behaviour.